Gender Disparities and School Climate: Key Factors in Understanding Bullying on Islamic Junior High School Students - Munjiah, Munjiah; Aziz, Rahmat (Program Studi Pendidikan Agama Islam, 2023)
This study aimed to test two main hypotheses regarding bullying in schools. The first hypothesis was that male and female students significantly differed in bullying behavior. The second hypothesis was that school climate significantly influenced bullying. This article used a quantitative design to examine gender and school climate differences in student bullying behavior. Data were obtained through the scale of school climate and bullying. The subjects were 150 (75 males and 75 females) Islamic junior high school students in East Java. The data were analyzed using variance analysis and regression analysis. The results exhibited a difference between males and females in terms of bullying. School climate affected bullying, both overall and in every aspect. Among the five aspects of school climate tested, only student relations had a significant negative effect on bullying. This study indicates that student relations are crucial in bullying and recommends specific interventions to improve safety and inclusivity.